Germination response of palm seeds on a two-way thermogradient plate - Sales Batista, Gisele; Vieira Ferraz, Marcos; Bachin Mazzini-Guedes, Renata; Pritchard, Hugh; Rex Marks, Timothy; Fernandes Lopes Pivetta, Kathia (Revista Ceres, 2023)
Palm trees are propagated almost exclusively by seeds and each species germinates under a certain temperature range. In this sense, the two-way thermogradient plate may be used to determine temperature limits for germination and seed response to temperature. The objective was to define the alternating temperature regime promoting higher and faster seed germination of Carpentaria acuminata and Phoenix canariensis palms using a two-way thermogradient plate. This equipment allowed 64 combinations of alternating and constant temperatures, ranging from 6.97 to 36.42 oC for C. acuminata, and 7.96 to 35.94 oC for P. canariensis. Seeds were sown in Petri dishes (25 x 9 cm) containing 1% water agar. Linear regressions were estimated to determine cardinal temperatures. After 50 days, non-germinated seeds were transferred from the two-way thermogradient plate to a germination chamber at 30 °C. The temperature regime promoting highest seed germination percentage of C. acuminata was 30.45/33.00 °C (day/night), with minimum, optimum, and maximum temperatures of 9.13, 28.53, and 36.33 °C, respectively. For seed germination of P. canariensis, the most appropriate temperature regime was 29.77/17.93 °C (day/night), with minimum, optimum, and maximum temperatures of 9.53, 28.03, and 35.43 °C, respectively.